Relationship of Lipid Profile with Wagner Severity Level in Diabetic Feet at General Hospital Dr. M. Djamil Padang - Yunes Ario; Raflis Rustam; Vendry Rivaldi (Biomedical Journal of Indonesia, 2021)
Introduction Diabetic foot is an erosion or injury to the epidermis or the distal sole of the foot and the base of the foot in people with diabetes mellitus (DM). Diabetic foot is a major cause of limb amputation in non-traumatic cases. Per year, as many as 2-3% of people with diabetes experience complications of diabetic foot. The prevalence of DM sufferers with diabetic foot is 20-40% in developing countries. In Indonesia, the prevalence of DM sufferers with diabetic foot is around 15% with 32% mortality rate. One factor plays an important role in predisposing the occurrence of diabetic foot is the lipidprofile. The aim ofthis study was to determine the correlation between lipid profile and Wagner Severity Level on diabetic foot patients at Dr. M. Djamil Central Public Hospital, Padang in the period of July 2020 to December 2020. M ethod: This research is an observational analytic study with cross sectional analytic design. The research sample of 47 cases was taken by non-probability sampling with the consecutive sampling method. This research is an observati onal analytic study with cross sectional analytic design. The research sample of 47 case s was taken by non-probability sampling with the consecutive sampling method. Result: There were 47 cases that met the inclusion criteria where the 51 -60 ye ars age group (55.3%) was the largest group in cases of diabetic foot. Of these groups, it was dominated by female patients, namely 31 patients (66.0%). Meanwhile, the Body Mass Index (BMI) was dominated by the group with BMI <25 kg/m2 with a total of 26 patients (55.3%). Diabetic foot patient at Dr. M Djamil Central Public Hospital Padang who underwent amputation was 25 patients (53.2%) where most of them, namely 40 patients (85.1%) had suffered from Diabetes Mellitus for> 5-10 years. The findings obtained based on the Wagner Severity Level were thatthe Wagner grade 3- 5 (heavy) group consisted of 24 people (51.1%) and Wagner 1-2 (mild) as many as 23 people (48.9%). The results of the bivariate test between lipid profile levels with Wagner Severity Level in diabetic foot patients showed a significant correlation as indicated by a p value <0.05. Conclusion: Wagner Severity Level which is getting higher in diabetic foot patients shows low HDL levels, high LDL levels andhigh levels of triglycerides in blood plasma.